Penerapan Kompres Hangat dalam Menurunkan Demam pada Pasien Kejang Demam - Sudariyekti, Arian Wirani; Irdawati, Irdawati (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effectiveness of applying warm compresses to reduce hyperthermia in children experiencing febrile seizures. This study method uses a case study method with a nursing process. The results of this study through the dependent T-test analysis, namely the P-Value, is 0.000, which is smaller than the significant level α (0.05). In conclusion, giving warm compresses to patients with febrile seizures has significantly reduced children's fever. Keywords: Hyperthermia, Febrile seizures, Warm compresses